2024
DOI: 10.1038/s41420-024-01853-3
|View full text |Cite
|
Sign up to set email alerts
|

8-Br-cGMP activates HSPB6 and increases the antineoplastic activity of quinidine in prostate cancer

Yuankang Feng,
Zhenlin Huang,
Fubo Lu
et al.

Abstract: Heat shock protein family B [small] member 6 (HSPB6), widely found in various muscles, has been recently identified as a tumor suppressor gene. However, its role in prostate cancer remains unexplored. Herein, we investigated the expression of HSPB6 in prostate cancer and its association with prognosis. Our findings revealed that HSPB6 downregulation in prostate cancer correlated with a poor prognosis. Moreover, we discovered that HSPB6 can be phosphorylated and activated by 8-Br-cGMP, leading to apoptosis in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…Feng et al investigated therapeutic activators and identified 8-Br-cGMP as capable of activating HSPB6 and inducing dephosphorylation of phosphorylated Cofilin, eliciting apoptosis in PCa cells. Notably, the synergistic effect of 8-Br-cGMP and quinidine notably bolstered HSPB6 transcription levels, effectively restraining PCa growth and offering promising prospects for PCa treatment ( Feng et al, 2024 ). Overexpression of miR-608 targets RAC2/PAK4/LIMK1/cofilin, thereby impeding PCa progression (X.…”
Section: Actin Filament Severing In Pcamentioning
confidence: 99%
“…Feng et al investigated therapeutic activators and identified 8-Br-cGMP as capable of activating HSPB6 and inducing dephosphorylation of phosphorylated Cofilin, eliciting apoptosis in PCa cells. Notably, the synergistic effect of 8-Br-cGMP and quinidine notably bolstered HSPB6 transcription levels, effectively restraining PCa growth and offering promising prospects for PCa treatment ( Feng et al, 2024 ). Overexpression of miR-608 targets RAC2/PAK4/LIMK1/cofilin, thereby impeding PCa progression (X.…”
Section: Actin Filament Severing In Pcamentioning
confidence: 99%